Ewing’s Sarcoma Cancer Stem Cell Targeted Therapy - Todorova, Roumiana (Current Stem Cell Research & Therapy, 2014)
Ewing`s sarcoma (ES) family of tumors (ESFTs) are round cell tumors of bone and soft tissues, afflicting children and young adults. This review summarizes the present findings about ES cancer stem cell (CSC) targeted therapy: prognostic factors, chromosomal translocations, initiation, epigenetic mechanisms, candidate cell of ES origin (Mesenchymal stem cells (MSCs) and Neural crest stem cells (NCSCs)). The ES CSC model, histopathogenesis, histogenesis, pathogenesis, ES mediated Hematopoietic stem progenitor cells (HSPCs) senescence are also discussed. ESFTs therapy is reviewed concerning CSCs, radiotherapy, risk of subsequent neoplasms, stem cell (SC) support, promising therapeutic targets for ES CSCs (CSC markers, immune targeting, RNAi phenotyping screens, proposed new drugs), candidate EWS-FLI1 target genes and further directions (including human embryonic stem cells (hESCs)). Bone marrowderived human MSCs are permissive for EWS-FLI1 expression with transition to ESFT-like cellular phenotype. ESFTs are genetically related to NCSC, permissive for EWS-FLI1 expression and susceptible to oncogene-induced immortalization. Primitive neuroectodermal features and MSC origin of ESFTs provide a basis of immune targeting. The microRNAs profile of ES CSCs is shared by ESCs and CSCs from divergent tumor types. Successful reprogramming of differentiated human somatic cells into a pluripotent state allows creation of patient- and disease-specific SCs. The functional role of endogenous EWS at stem cell level on both senescence and tumorigenesis is a link between cancer and aging. The regulatory mechanisms of oncogenic activity of EWS fusions could provide new prognostic biomarkers, therapeutic opportunities and tumor-specific anticancer agents against ESFTs.
Keywords: Cancer stem cells